Cloud computing in e-commerce in palestine: legal issues and challenges - Hasan, Yahya Y. F.; Zulhuda, Sonny (2015)
This paper will discuss these challenges of using cloud computing within ecommerce including the liability surrounding the data security and privacy in the cloud. In addition, this paper seeks to clarify the provider’s liability for loss or destruction of the information during cloud computing. Furthermore, this study aims to examine the legality of unfair contract terms in the cloud computing contracts under the Palestinian laws. This study mainly used the analytical and library research to examine the main issues of cloud computing. The laws of Palestine and the Directive 95/46/EC are used in this study to clarify the legal positions on the relevant issues above. It is found from this study that the current laws in Palestine are inadequate to regulate the cloud computing issues.